2001
DOI: 10.1074/jbc.m102156200
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane-4 Superfamily Proteins Associate with Activated Protein Kinase C (PKC) and Link PKC to Specific β1 Integrins

Abstract: Translocation of conventional protein kinases C (PKCs) to the plasma membrane leads to their specific association with transmembrane-4 superfamily (TM4SF; tetraspanin) proteins (CD9, CD53, CD81, CD82, and CD151), as demonstrated by reciprocal co-immunoprecipitation and covalent cross-linking experiments. Although formation and maintenance of TM4SF-PKC complexes are not dependent on integrins, TM4SF proteins can act as linker molecules, recruiting PKC into proximity with specific integrins. Previous studies sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
292
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(303 citation statements)
references
References 71 publications
(61 reference statements)
10
292
1
Order By: Relevance
“…Therefore, we performed the present study to clarify the signal pathway of MRP-1/CD9, which might lead to new strategies of treatment for cancer patients. MRP-1/CD9 is considered to exert its biological functions by forming a functional complex with integrin a3b1 and integrin a6b1 (Zhang et al, 2001b;GutierrezLopez et al, 2003). In fact, a previous clinical study has revealed that reduced integrin a3 expression is also a poor prognostic factors in patients with lung adenocarcinomas .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we performed the present study to clarify the signal pathway of MRP-1/CD9, which might lead to new strategies of treatment for cancer patients. MRP-1/CD9 is considered to exert its biological functions by forming a functional complex with integrin a3b1 and integrin a6b1 (Zhang et al, 2001b;GutierrezLopez et al, 2003). In fact, a previous clinical study has revealed that reduced integrin a3 expression is also a poor prognostic factors in patients with lung adenocarcinomas .…”
Section: Discussionmentioning
confidence: 99%
“…Tetraspanins lack intrinsic activity and their effects are mediated by protein interactions. Several different proteins have been shown to associate with CD82 (Yunta and Lazo, 2003), including a3b1, a4b1, a5b1, and a6b1 integrins (Berditchevski and Odintsova, 1999;Berditchevski, 2001;Yunta and Lazo, 2003); the serine/threonine kinase PKCa (Berditchevski and Odintsova, 1999;Berditchevski, 2001;Zhang et al, 2001); B-cell receptors CD4, CD8, and CD19 (Imai et al, 1995;Mannion et al, 1996;Hammond et al, 1998); other tetraspanins including CD81, CD63, and CD9 (Vogt et al, 2002); receptor tyrosine kinases EGFR and ErbB2 (Odintsova et al, 2000(Odintsova et al, , 2003; an Ig super family molecule EW12 (Zhang et al, 2003b); and a newly identified tetraspanin molecule, kitenin, which is expressed in gastric cancers (Lee et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…These tetraspanin complexes link extracellular interactions to the second messenger system. For example, CD81 and other tetraspanins can form a molecular complex with integrins to regulate interactions of the cell with the extracellular matrix, affecting second messenger systems (phosphatidylinositol 4-kinase) and eventually modulating the mitotic activity of the cell [1,2,20]. To date, the data indicate that CD81 is part of a molecular switch that controls reactive gliosis and the proliferation of non-neuronal elements in the retina.…”
mentioning
confidence: 99%